Sustainable Tourism in Indonesia’s Ring of Fire: Toward Ecological Justice and Green Energy - Manumayoso, Bambang; Jaelani, Abdul Kadir; Firdaus , Wan Mohd Khairul; Ogli , Tojiboev Akbar Zafar (Lembaga Contrarius Indonesia, 2025)
Indonesia’s Ring of Fire holds vast renewable energy and geotourism potential, but this potential can only be optimized through legal governance that is ecologically just. Current governance remains dominated by a sectoral, fragmented regulatory framework that not only causes disharmony but also exacerbates conflicts of interest between energy, tourism, and environmental sectors. This study develops an integrated legal and policy framework based on ecological justice and Pancasila justice, positioning them as complementary paradigms for reconciling development goals with environmental sustainability and social equity. Using a normative legal method that combines statutory interpretation, conceptual approaches, and case analysis of geothermal and geotourism projects. The results show that, first, Indonesia’s Ring of Fire holds significant potential for sustainable tourism and renewable energy, yet progress is constrained by fragmented regulations, limited community participation, and the absence of ecological justice in the legal framework. Second, these challenges highlight the urgent need for comprehensive governance transformation that integrates energy, environment, and tourism under a unified legal framework, recognizes nature as a legal subject, and empowers local communities as primary agents of sustainable development. Third, the proposed policy framework promotes sustainable tourism through legal reform, collaborative governance, and ecological justice by revising and harmonizing Tourism, Energy, and Environmental Laws.